2021
DOI: 10.1099/ijsem.0.004903
|View full text |Cite
|
Sign up to set email alerts
|

Flavobacterium muglaense sp. nov. isolated from internal organs of apparently healthy rainbow trout

Abstract: Two yellow-pigmented isolates, F-60T and F-392, were isolated from the internal organs of an apparently healthy rainbow trout (Oncorhynchus mykiss). The strains were identified as members of the genus Flavobacterium based on the results of 16S rRNA gene sequence analysis. Strains F-60T and F-392 had the highest 16S rRNA gene sequence identity level of 97.4 % to the type strain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The most well-defined clades outside of Clade A (CCB) and Clade F (F. psychrophilum) were Clades C and G. Clade C contained a type-strain from a species associated only with healthy rainbow trout outside of the US -F. muglaense (Duman et al, 2021). Salmonid isolates from CA and UT shared 99-100% 16S rRNA gene similarity to the type-strain, and the phylogenetic tree topography indicates high similarity within the gyrB gene as well.…”
Section: Discussionmentioning
confidence: 97%
“…The most well-defined clades outside of Clade A (CCB) and Clade F (F. psychrophilum) were Clades C and G. Clade C contained a type-strain from a species associated only with healthy rainbow trout outside of the US -F. muglaense (Duman et al, 2021). Salmonid isolates from CA and UT shared 99-100% 16S rRNA gene similarity to the type-strain, and the phylogenetic tree topography indicates high similarity within the gyrB gene as well.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, previous research has shown that while MALDI-TOF MS is capable of identifying some common fish pathogens, the current database falls short in identifying uncommon and novel species. The identification of novel fish pathogens in the past few years (Duman et al 2020(Duman et al , 2021b(Duman et al , 2021aMulet et al 2021;Saticioglu et al 2021aSaticioglu et al , 2021bSaticioglu et al , 2021c has clearly demonstrated that MALDI-TOF MS analysis alone would not suffice in microbial identification. Recent studies have demonstrated that while this method can be used for the identification of wellknown species and species for which the method's success has been confirmed, the complementary support of MALDI-TOF MS with phenotypic tests and basic molecular methods is required nonetheless.…”
Section: Matrix-assisted Laser Desorption/ionization Time-of-flight M...mentioning
confidence: 99%
“…The identification of novel fish pathogens in the past few years (Duman et al. 2020, 2021b, 2021a; Mulet et al. 2021; Saticioglu et al.…”
Section: Whole‐cell Protein Analysismentioning
confidence: 99%
“…in seabreams; furthermore, the fungal pathogens Saprolegnia spp. and the parasites Trichodina , Chilodonela , Argulus , and Ergasilus , as well as Leeches have been known for a long time ( Kim et al, 2017 ; Buján et al, 2018 ; Duman et al, 2021 ; Abd El-Hack et al, 2022 ; Shahin et al, 2022 ; Ibrahim et al, 2022a , b ). However, many unknown or emerging etiological diseases still appear frequently in aquatic farms, seriously affecting the development of aquaculture ( Shahin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%